2019
DOI: 10.1111/ics.12594
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the secret life of skin ‐ with the microbiome you never walk alone

Abstract: The human skin microbiome has recently become a focus for both the dermatological and cosmetic fields. Understanding the skin microbiota, that is the collection of vital microorganisms living on our skin, and how to maintain its delicate balance is an essential step to gain insight into the mechanisms responsible for healthy skin and its appearance. Imbalances in the skin microbiota composition (dysbiosis) are associated with several skin conditions, either pathological such as eczema, acne, allergies or dandr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 126 publications
(157 reference statements)
1
49
0
2
Order By: Relevance
“…The implications for wound healing and protection against potential pathogens or environmental conditions highlight a crucial role of skin homeostasis. Indeed, recent studies have identified associations between shifts in these commensal populations and physiological changes, such as aging and diverse dermatological diseases, not only in humans but in all vertebrates [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The implications for wound healing and protection against potential pathogens or environmental conditions highlight a crucial role of skin homeostasis. Indeed, recent studies have identified associations between shifts in these commensal populations and physiological changes, such as aging and diverse dermatological diseases, not only in humans but in all vertebrates [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of information on bacterial species from 19 different skin sites and various skin-specific niches including anaerobic/aerobic niches and carbon- and sulfur-rich/-limiting niches in the skin microbiome database was very important for comprehensive training and achieving higher prediction accuracy. It was observed that the skin microbiome database had a higher representation of aerobic species because the metagenomic studies so far have been carried out majorly for the aerobic niches than the anaerobic niches due to the difficulty associated with anaerobic niches in sampling, isolation, and cultivation ( Sfriso et al., 2020 ). Another key aspect of SkinBug is the inclusion of all the well-annotated and manually curated reactions of the KEGG database and their primary substrates for the construction of training set, analysis, and modeling.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall number of microorganisms present on the skin is held relatively constant under normal conditions ( Davis, 1996 ). The commensal relationship between cutaneous tissue and the diverse community of microorganisms plays a critical role in barrier protection from invading pathogenic microorganisms, homeostasis, and the adaptive immune response ( Dréno et al, 2016 ; Sfriso et al, 2020 ).…”
Section: The Effects Of Radiation On the Microbiomementioning
confidence: 99%